Love Of Money, Organizational Commitment, Leadership Morale, Work Environment and Religious Beliefs on Fraud Intention A Study on Bank Bengkulu Employees - Eddy Surantha (Jurnal Akuntansi, 2022)
This study aims to examine the effect of Love Of Money, Organizational Commitment, Moral Leadership, Work Environment and Religious Beliefs on Fraud Intention where the object of research used is Bengkulu Bank employees. The employees of Bengkulu Bank who were selected as the research sample used the random sampling method, namely Bengkulu Bank employees who worked at the head office, main branches, main branches and cash offices located in both Bengkulu City and the regencies in Bengkulu Province. The total population is 700 employees of Bank Bengkulu and using the Slovin formula, the number of respondents that should be used in this study is 88 respondents. From the questionnaires sent as many as 88 respondents, the number of questionnaires returned was 70 respondents and the number of questionnaires that could be processed was 64 respondents (respondent rate 79.55%). Testing all hypotheses using Smart PLS where the hypotheses tested are 5 hypotheses. The test results on all the hypotheses tested show that the work environment has a negative effect on fraud intention, while the influence of Love Of Money, Organizational Commitment, Leadership Morale and Religious Beliefs have no effect on fraud intention.